Variation of concrete compressive strength of f'c 210 kg/cm² when incorporating abutments and spirals as transverse reinforcements in the region of Cajamarca-2022 (LACCEI, 2024)
The main objective of this research was to determine the variation of the compressive strength of concrete specimens of f'c 210 kg/cm2 by incorporating stirrups and spirals as transversal reinforcements in different distributions in the Cajamarca-2022 region. The methodology followed consisted of an experimental design, in which 24 specimens were prepared for curing times at 7, 15, 28 days, having a total of 72 samples. ASTM C39 was followed to determine the strength of the cylindrical cores. As a result, it was determined that the average strength of the samples with spirals exceeded the values achieved for the samples with stirrups, this in the three curing times, thus obtaining for the 7-day age a maximum strength of 209. 263 kg/cm2 at a spacing of 8.33 cm, for the age of 14 days, a resistance of 222.654 kg/cm2 at a spacing of 6.25 cm and at the age of 28 days a maximum resistance of 315.107 kg/cm2 at a spacing of 5.00 cm, all these when incorporating spirals. Thus, when comparing results, it was observed that the strength variation of the specimens with spiral reinforcement exceeded that of the specimens reinforced with stirrups.